1990
DOI: 10.1021/jm00164a063
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and antiviral activity of 3'-heterocyclic substituted 3'-deoxythymidines

Abstract: Various 3'-deoxythymidine analogues with an heterocyclic five-membered ring in the 3'-erythro position have been synthesized. The pyrrol-1-yl (3) and the 1,2,4-triazol-4-yl (5) compounds were synthesized from 1-(3-amino-2,3-dideoxy-beta-D-erythro-pentofuranosyl)thymine. The pyrazol-1-yl (16a), imidazol-1-yl (16b), and 1,2,4-triazol-1-yl (16c) derivatives were obtained by epoxide opening of the corresponding 1-(2,3-anhydro-beta-D-lyxofuranosyl)thymines followed by 2'-deoxygenation. Only the 3'-pyrrol-1-yl deriv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

1990
1990
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 5 publications
1
15
0
Order By: Relevance
“…The most promising agents of this class of drugs are 3'deoxy DNA nucleosides and 3 -azole derivatives [8][9][10][11][12], which might fulfill the need of this strategy. Herdewijin et al [13] and Hirota et al [14] have reported the synthesis of compounds, in which the azide group of AZT is transformed to a triazole ring 3, but these compounds did not show appreciable activity against HIV. Our work here is concerned with the synthesis of new 3 -azole analogues from the cycloaddition of 5 -acetyl-3 -deoxy-3 -isothiocyanatothymidine 9 and 3 -cyano-analogue 19, prepared from the antiviral nucleoside CNT [4,5], with some reactive cumulenes.…”
Section: Introductionmentioning
confidence: 99%
“…The most promising agents of this class of drugs are 3'deoxy DNA nucleosides and 3 -azole derivatives [8][9][10][11][12], which might fulfill the need of this strategy. Herdewijin et al [13] and Hirota et al [14] have reported the synthesis of compounds, in which the azide group of AZT is transformed to a triazole ring 3, but these compounds did not show appreciable activity against HIV. Our work here is concerned with the synthesis of new 3 -azole analogues from the cycloaddition of 5 -acetyl-3 -deoxy-3 -isothiocyanatothymidine 9 and 3 -cyano-analogue 19, prepared from the antiviral nucleoside CNT [4,5], with some reactive cumulenes.…”
Section: Introductionmentioning
confidence: 99%
“…Most of these compounds have shown little or no activity (Van Aershot et sl., 1989;Wigerinck et a/., 1990;Mikhailopulo et a/., 1991). We have previously studied various S-substituted 2'-deoxyuridines and cytosines, which also exhibited rather low or no antiviral activity (Peters et a/., 1992).…”
Section: Introductionmentioning
confidence: 99%
“…These are the syntheses with the reduction of 3'-azido-3'-deoxythymidine [7][8][9][16][17][18][19][20][21][22][23][24] and syntheses through the alkylation of various nitrogen-containing compounds by 3'-sulfonate derivatives of thymidine [25].…”
Section: Resultsmentioning
confidence: 99%